The Potentiality of the Teaching-Learning Objects (T-LO) and Teaching-Learning Virtual Environments (T-LVE) - Mallmann, Elena Maria; Nunes, Ingrid Kleist Clark (International Journal of Emerging Technologies in Learning (iJET), 2008)
The pedagogical mediation in Distance Education (DE) is supported by principles such as interaction, cooperation and autonomy. We have investigated the potentiality of the hypermedia T-LVE and in the T-LO, utilized to implement these pedagogical principles. The Meaningful Learning Theory categories have been methodologically chosen to analyze the elaboration and implementation process of potentially meaningful didactic materials with interactive tools like Lesson (Moodle module) and Articulate Present/Quizmaker (integrated to Power Point). The theoretical-methodological results about the methods and tools of content adaptation in T-LVE and T-LO clearly demonstrate the presence of the hypermedia character in these resources. We highlight that these interactive tools allow the systematized elaboration of hypermedia didactic materials. The Lesson and the Articulate provide connection between technological mediators, pedagogical principles and curricular contents. T-LVE and T-LO became potentially meaningful due to a didactic-methodological plan that includes progressive differentiation, integrative reconciliation, sequential organization and consolidation of the curricular contents.